Technological innovation to support the decision-making process for open pit mining: the application of technological models and semi-mobile in-pit crushing and conveying scenario\'s evaluation. - Nunes, Rodrigo Augusto (2019)
This work presents two innovative ways to evaluate mining projects. The first is the application of a Technological Model in a copper-gold mine and the second is a decision making model to evaluate the benefit of semi-mobile in pit crusher and conveyor alternatives during the early stages of mining projects. In order to improve the process and to maximize the production and/or value of a mining project, there needs to be an integration of the geology, the mine plan, the processing and the geometallurgy data. In order to accomplish this, a new methodology is proposed for the creation of a technological model. This model can be interpreted as the consolidation of the different models required for a better understanding of the geological and technical information of the deposit. This concept was developed and applied at a copper and gold mine site located in Brazil. Based on the evaluation of different blasting and mill productivity scenarios through a pit-to-plant approach, it was possible to obtain operational short-term gains such as a 10.7% increase in the plant production rate and a 2.2% increase in the crusher\'s feed rate with little or no capital investment. Another important issue faced by mining companies is related to material handling. A significant cost in the operating budget of most mining operations arises from purchasing and maintaining haulage trucks. Recently, in-pit crushing and conveying (IPCC) has been subject to research because of its potential to reduce haulage costs. A decision-making model was created to identify early on in a project whether or not the semi-mobile IPCC (SMIPCC) is an appropriate alternative to the conventional truck haulage based on the loading and hauling approaches. The method is based on cost analysis and the evaluation of environmental impacts, being successfully tested at an existing open-pit mine, where the results indicated that the IPCC was the most cost-effective option for the operation. Although the IPCC\'s initial CAPEX was 60% higher than the conventional approach, the IPCC\'s OPEX was 43% lower, resulting in a 28% reduction of the life-of-mine net present cost (NPC).